IDENTIFICATION OF SELF CONCEPT AND ENTREPRENEURIAL INTERESTS AND FACTORS INHIBITING ENTREPRENEURSHIP - Toto Sugiarto; Ganefri Ganefri; Asmar Yulastri; Dwi Sudarno Putra; Wagino Wagino (Universitas Gunadarma, 2023)
This study aims to identify self-concept and interest in entrepreneurship, and inhibiting factors in entrepreneurship for students of the Automotive Engineering Department, Faculty of Engineering, Padang State University. The research subjects are students of the entry year 2019, 2020, 2021, and 2022, with a total of 100 students. The data collection method used a questionnaire about self-concept, interest in entrepreneurship and inhibiting factors in entrepreneurship. The data analysis method used is descriptive analysis. The results of the analysis show that the entrepreneurial self-concept of students is 88.64%, so it can be interpreted is very high. The results of the analysis of interest in entrepreneurship are 81.06%, this shows a very high interest in students to become entrepreneurs. Finally, the results of the analysis of the inhibiting factors for students in entrepreneurship are 68.24%, this shows that the inhibiting factors for entrepreneurship are high. Efforts that must be made by the government are in the form of policies that support entrepreneurial activities. The role of the business world and industry is in the form of capital support and sharing experiences with students, while universities must create entrepreneurship programs that can be used as a forum for entrepreneurship training by students.